Dehydration of CO2-α-cyclodextrin complex powder by desiccant adsorption method and its release properties. (16th November 2016) - Ho, Thao M.; Howes, Tony; Bhandari, Bhesh R.
Abstract: Stability and release properties of CO2 -α-cyclodextrin complex powder prepared by solid encapsulation (water activity, a w ≈ 0.95) followed by moisture removal using silica gel and CaCl2 desiccants during post-dehydration were investigated. The results showed that CaCl2 reduced a w much faster than silica gel did under the same conditions. After approximately 60 h, a w of complex powders reduced using silica gel was almost constant at 0.247 (±0.012), while those treated with CaCl2, a w was 0.225 (±0.005) and had not yet reached their lowest value. Moisture adsorption by silica gel and CaCl2 also led to a decrease in the CO2 concentration of complex powder (higher decrease for silica gel adsorption) without affecting the structure and morphology of complex powder. The CO2 release properties of CaCl2 - a w -reduced complex powder at different relative humidities (32.73, 52.86, 75.32 and 97.30% RH), liquid environments (water and oil) and packaging methods (normal and vacuum) were also studied.